-10+3t=5-2t

Simple and best practice solution for -10+3t=5-2t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10+3t=5-2t equation:


Simplifying
-10 + 3t = 5 + -2t

Solving
-10 + 3t = 5 + -2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '2t' to each side of the equation.
-10 + 3t + 2t = 5 + -2t + 2t

Combine like terms: 3t + 2t = 5t
-10 + 5t = 5 + -2t + 2t

Combine like terms: -2t + 2t = 0
-10 + 5t = 5 + 0
-10 + 5t = 5

Add '10' to each side of the equation.
-10 + 10 + 5t = 5 + 10

Combine like terms: -10 + 10 = 0
0 + 5t = 5 + 10
5t = 5 + 10

Combine like terms: 5 + 10 = 15
5t = 15

Divide each side by '5'.
t = 3

Simplifying
t = 3

See similar equations:

| -4+7n=-8n+7(8+5n) | | 2r+9=-7r | | 10h+4=8h+9+3h | | w+w-4+w+w-4=112 | | -3/4u=-6 | | log[4](x+2)=log[4](3x-12) | | 2x-3=1-14 | | -22=4v-6 | | -3+9r=10r-10 | | 5m^2+9m+20=0 | | 5u+8=23 | | x^2-60x-500=0 | | -9-5x=-(1-2x)-5x | | 2e^4x=700 | | 4n-6=1+5n | | 9u-8=10u | | 8m=6m-29 | | 3(4x+1)-5= | | 279-v=83 | | 257=191-v | | 27/-9/8 | | 155=-x+83 | | -5j=8-6j | | 40.95=9g+3.78 | | -4(y+5)-(y+5)= | | b-2+4=17 | | 4x-3=12+5 | | -29+6n=4+5(1+5n) | | 16-8x=5x+9 | | 40-3y=5y | | -3(u+5)+5u= | | Z/3-z=6 |

Equations solver categories